Quantifying risk assessments for monitoring control and surveillance of illegal fishing. (4th March 2022) - Ford, Jessica H; Wilcox, Chris
Abstract: One of the key international efforts to reduce Illegal, Unreported, and Unregulated (IUU) fishing is the United Nations Food and Agriculture Organization's Port State Measures Agreement. The agreement is designed to close off the opportunities for non-compliance, such as vessels engaging in illegal practices to land their catch. However, with thousands of vessels at sea and relatively limited inspection capacity, enhanced communication and information sharing to identify priority high-risk vessels is fundamental to successful implementation. Moving from traditional qualitative to quantitative risk assessments is one key step in ensuring the effective and efficient implementation. Risk profiling is in its infancy in the field of IUU fishing. Here, we present a transparent and repeatable method for eliciting quantitative weightings for indicators of IUU fishing using the Analytical Hierarchy Process. The method highlights the improvements in discrepancy with quantitative rankings, in comparison to traditional qualitative approach used, and the inherent ambiguity associated. This method can help to improve decision support systems used by fisheries surveillance agencies around the world. Knowing which vessels are high-risk is key to decision-making. Working towards a quantitative risk-based approach is fundamental step to improving oversight and control of IUU.